Beam dynamics in an initial part of a high brightness electron linac - Ayzatsky, M.I.; Gutovsky, D.E.; Dovbnya, A.N.; Kushnir, V.A.; Mytrochenko, V.V.; Perezhogin, S.A. (Вопросы атомной науки и техники, 2001)
The paper is focused on problems of obtaining a bright electron beam in a system that includes a grid-controlled electron gun, a klystron type subharmonical buncher, a standing wave fundamental buncher with increasing accelerating field and a short travelling wave accelerating section. Beam focusing is provided by a longitudinal solenoidal magnetic field. It was shown that the proposed system can provide electron bunches with a peak current more than 100 A and normalized r.m.s. emittance no more than 12 π∙mm∙mrad.